2013
DOI: 10.1007/s00264-013-1781-0
|View full text |Cite
|
Sign up to set email alerts
|

Is etoricoxib effective in preventing heterotopic ossification after primary total hip arthroplasty?

Abstract: Purpose Heterotopic ossification is a common complication after total hip arthroplasty. Non-steroidal anti-inflammatory drugs (NSAIDs) are known to prevent heterotopic ossifications effectively, however gastrointestinal complaints are reported frequently. In this study, we investigated whether etoricoxib, a selective cyclo-oxygenase-2 (COX-2) inhibitor that produces fewer gastrointestinal side effects, is an effective alternative for the prevention of heterotopic ossification. Methods We investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Prostaglandin E 2 is a major contributor to heterotopic ossification formation, fracture-healing, and bone regeneration [47][48][49][50][51][52][53][54][55][56][57][58][59] . Numerous recommendations exist with regard to dosing; indomethacin, a nonselective cyclooxygenase (COX)-1 and COX-2 inhibitor, is commonly administered at an oral dose of 75 mg twice per day or 25 mg three times per day for three to six weeks postoperatively 15,60,61 .…”
Section: Management Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E 2 is a major contributor to heterotopic ossification formation, fracture-healing, and bone regeneration [47][48][49][50][51][52][53][54][55][56][57][58][59] . Numerous recommendations exist with regard to dosing; indomethacin, a nonselective cyclooxygenase (COX)-1 and COX-2 inhibitor, is commonly administered at an oral dose of 75 mg twice per day or 25 mg three times per day for three to six weeks postoperatively 15,60,61 .…”
Section: Management Prophylaxismentioning
confidence: 99%
“…Oxygen tension, pH, micronutrients, and mechanical stimuli also impact bone formation 54 . Hypoxia-inducible factor 1-alpha (HIF-1a) is a key transcriptional regulator of the cellular response to ischemia through stimulation of vascular endothelial cell precursors 99,100 (Fig.…”
Section: Local Microenvironmentmentioning
confidence: 99%
“…Lavernia et al [59] found celecoxib significantly more effective for HO prophylaxis when given 200 mg twice/-day for 28 days after THA compared to control group. At this stage, some studies recommend an oral HO prophylaxis for 4-6 weeks, whereas recent studies, as mentioned above, found 7-20 days to be effective, too [6,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…indomethacin, diclofenac) [3,57]. Brunnekreef et al [58] found etoricoxib to be effective for HO prevention after cemented THA when given for 7 days. Lavernia et al [59] found celecoxib significantly more effective for HO prophylaxis when given 200 mg twice/-day for 28 days after THA compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…by Brunnekreef et al [1] published in International Orthopaedics with great interest.In this study, the authors proved that etoricoxib, a selective cyclo-oxygenase-2 (COX-2) inhibitor, was effective for the prevention of heterotopic ossification (HO) following total hip arthroplasty (THA). However, we have several opinions which we would like to communicate with the authors.…”
mentioning
confidence: 99%